2012
DOI: 10.1016/j.rbmo.2012.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Roles of antioxidant enzymes in corpus luteum rescue from reactive oxygen species-induced oxidative stress

Abstract: Progesterone produced by the corpus luteum (CL) regulates the synthesis of various endometrial proteins required for embryonic implantation and development. Compromised CL progesterone production is a potential risk factor for prenatal development. Reactive oxygen species (ROS) play diverse roles in mammalian reproductive biology. ROS-induced oxidative damage and subsequent adverse developmental outcomes constitute important issues in reproductive medicine. The CL is considered to be highly exposed to locally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(67 citation statements)
references
References 111 publications
2
58
0
2
Order By: Relevance
“…These observations support our earlier findings (Liptak et al 2005) that activated immune cells may contribute a factor (or factors) that impair steroidogenesis in response to LH. It is known that activated monocytes produce inflammatory cytokines, nitric oxide, and reactive oxygen species (Murray & Wynn 2011, Zhou et al 2014) all of which may contribute individually or in combination to the inhibition of progesterone synthesis (Al-Gubory et al 2012, Quirk et al 2013, Skarzynski et al 2013). In the in vivo setting, activated monocytes may also secrete matrix metalloproteinases that contribute to the degradation of the extracellular matrix (Murray & Wynn 2011), which could facilitate the recruitment of additional inflammatory cells to the regressing corpus luteum.…”
Section: Discussionmentioning
confidence: 99%
“…These observations support our earlier findings (Liptak et al 2005) that activated immune cells may contribute a factor (or factors) that impair steroidogenesis in response to LH. It is known that activated monocytes produce inflammatory cytokines, nitric oxide, and reactive oxygen species (Murray & Wynn 2011, Zhou et al 2014) all of which may contribute individually or in combination to the inhibition of progesterone synthesis (Al-Gubory et al 2012, Quirk et al 2013, Skarzynski et al 2013). In the in vivo setting, activated monocytes may also secrete matrix metalloproteinases that contribute to the degradation of the extracellular matrix (Murray & Wynn 2011), which could facilitate the recruitment of additional inflammatory cells to the regressing corpus luteum.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, it has been shown that mitochondria generate ROS at an amount higher than their scavenging capacity 8 . O 2 • — is initially formed via a large number of pathways, including normal cellular respiration, the metabolism of arachidonic acid by lipoxygenases and cyclo-oxygenases and from inflammatory and endothelial cells 9 . The main sources of O 2 • — are respiratory complexes I (NADH dehydrogenase) and III (ubisemiquinone) located at the inner mitochondrial membrane, which generate a small amount of O 2 • — as a side product of electron transport during oxidative phosphorylation 10 .…”
Section: Reactive Oxygen Species and The Antioxidant Defense Systemmentioning
confidence: 99%
“…Without O 2 • — , the formation of nitrogen dioxide by the reaction of NO with oxygen is miniscule by comparison. There is no requirement for NO and O 2 • — to be produced within the same cell to form peroxinitrite, as NO can readily move through membranes and between cells 9, 21…”
Section: Reactive Oxygen Species and The Antioxidant Defense Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…ROS target the pathway and also act as second messengers in some reactions [22]. ROS are known to effect ovulation and implantation [23].…”
Section: Redox Cell Signalingmentioning
confidence: 99%